Mapping Vulnerability and Risk of Ghana's Coastline to Sea Level Rise. Issue 1 (2nd January 2017) - Boateng, Isaac; Wiafe, George; Jayson-Quashigah, Philip-Neri
ABSTRACT: Coastal erosion and flooding are major threats to coastal dwellers, and the situation is predicted to worsen as a result of the impacts of climate change and associated sea level rise. In order to identify the level of vulnerability of various sections of Ghana's coastline for planning and future hazard management, a coastal vulnerability index approach was adopted for the creation of the relative vulnerability map. The coastal vulnerability variables used include geomorphology, coastal elevation, geology, local subsidence, sea level rise, shoreline change rates, mean tidal range, mean wave height and population density of the coastal areas. Risk factors were assigned to the various variables, and all the factors were combined to calculate the coastal vulnerability for the coastal front of each administrative district along the coast. The outcome was used to produce a vulnerability index map of coastal districts in Ghana. The results revealed that parts of the central coast and the eastern coasts of Ghana were the most vulnerable. It was identified that about 50% of the 540km shoreline of Ghana is vulnerable. This assessment will facilitate the long-term adaptation planning and hazard mitigation to inform the management of Ghana's coast.